Prevalence of problematic internet use in Slovenia - Macur Mirna; Király Orsolya; Maraz Aniko; Nagygyörgy Katalin; Demetrovics Zsolt (Sciendo, 2016)
Internet use is an integral part of our everyday activities; however, Internet use may become problematic and harmful in a minority of cases. The majority of reported prevalence rates of problematic Internet use refer to adolescent samples, whereas epidemiological studies on representative adult populations are lacking. This study aimed to reveal the prevalence and characteristics of problematic Internet use in Slovenia.